Insufficient evidence for vitamin E in Alzheimer's disease - Hermann, Dirk M. (Alzheimers Dement (N Y), 2016)
Vitamin E has recently been suggested to slow down the progression of Alzheimer's disease. Current evidence is based on three studies in patients with Alzheimer's disease and one study in patients with mild cognitive impairment which all together included only 1756 patients. Importantly, two of these studies were negative, and the two other studies had severe methodological weaknesses that preclude more definite interpretation. Based on the notion from patients suffering from cerebrovascular diseases that vitamin E may induce serious side effects (i.e., hemorhagic stroke), vitamin E cannot be recommended for use in Alzheimer's patients.